Introduction to economic history 1750 - 1950 - "Cole, G.D.H" (London, 1952)
This book covers the following topics The nature of modern industrial society; Two hundred years ago; The Industrial revolution; The development of France and Germany; The growth of the United states; Economic Imperialism; The Emergence of Russia etc.
Keywords: Economics